PEMBAYARAN REKENING LISTRIK PASCABAYAR DI PT. PLN PERSERO BATUSANGKAR MENURUT UNDANG-UNDANG NOMOR 08 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN DAN HUKUM EKONOMI SYARIAH - Gusti Marlina (Tamwil, 2017)
The main problem in this research is Payment of Postpaid Electricity Account at PT. PLN Persero Batusangkar According to law Number 08 of 1999 on consumer Protection and Sharia Economic Law. This study aims to determine whether the system of electricity bill payment at PT. PLN Persero Batusangkar has been in line with the existing laws in Indonesia and the view of Islamic Law. Type of research is field research. Data collection techniques used are observation, interviews, and documentation. Data analysis tecnique is done by data reduction, data presentation, and conclusion. From the research that has been done in the field can be concluded in the Aplication of Law Number 08 Year 1999 About Legal Protection Against Consumers in payment of electricity bill postpaind not in line with Law Number 08 of 1999 on the protection of consumer law contained in article 4 letter c stated that the right to information is correct, clear and honest about the condition and guarantee of goods and/or services. And Payment of Postpaid Electricity Account According to Sharia Economic Law is Gharar because Ujrah paid to PT. PLN Persero Batusangkar is not known value by one of the parties and this is not in line with the terms of Ujrah in Ijarah agreement and not fulfillment of one of the pillars in Ijarah agreement, thus the contract is not valid.